Involvement of the population of the USSR in providing assistance to families with children during the Great Patriotic War (on the example of the Baikal region) - Burdina, Daria Aleksandrovna (Исторический журнал: научные исследования, 2023)
The article discusses the issues of organizing assistance to Soviet families during the Great Patriotic War (1941-1945). In wartime conditions, accompanied by economic instability for the state, families with children, including military families, were in a difficult situation. Taking care of the Soviet family and the younger generation became the basis of the course of social policy, but the state could not always provide targeted assistance in time. That is why an important element of the organization of conditions for a stable situation of the population has become the involvement of collective farms, industrial and commercial enterprises, as well as individuals to assist families with children. The scientific novelty of the article consists in attracting a wide range of sources from the archives of the Republic of Buryatia and the Irkutsk region. Analysis of the documents showed that during the Great Patriotic War, the population helped those in need in various forms. In difficult times, the people acted unanimously and created various aid organizations: red Cross societies, charitable foundations, maternity and childhood committees. The population also helped those in need by accepting orphans, evacuated citizens and refugees for temporary residence. The enterprises did not stand aside. For the Baikal region, these measures were as important as for the rest of the USSR.